Off-stoichiometric nickel cobaltite nanoparticles: thermal stability, magnetization, and neutron diffraction studies - Verma, Seema; Kumar, Amit; Pravarthana, D.; Deshpande, Aparna; Ogale, Satishchandra B.; Yusuf, S. M. (Journal of Physical Chemistry C, 2014)
In the present investigation, we report a detailed examination of the effect of off-stoichiometry introduced in NiCo2O4 by adding excess cobalt. Thus, we compare and analyze the structural and magnetic properties of the Ni075Co2.25O4 and NiCo2O4 cubic systems. A low temperature combustion method was utilized to synthesize stoichiometric (NiCo2O4) and off-stoichiometric (Ni0.75Co2.25O4) nanoparticles on a large scale. The X-ray diffraction pattern for the sample annealed at high temperature (773 K) shows the presence of a much less intense NiO phase (similar to 2-5%) in Ni0.75Co2.25O4 as compared to that in the case of NiCo2O4 sample (similar to 15-20%). The Ni 2p and Co 2p XPS spectra reveal the coexistence of Ni2+, Ni3+, Co2+, and Co3+ species on the surface of both the NiCo2O4 and Ni0.75Co2.23O4 samples in differing proportions. In addition to the basic magnetic characterizations using PPMS, these were also analyzed by neutron diffraction. The off-stoichiometric Ni0.75Co2.25O4 sample shows an interesting magnetic phase conversion from frustrated dipolar system to an enhanced magnetic ordering upon annealing. Local moments on the lattice sites of NiCo2O4 and Ni0.75Co2.25O4 samples are further compared by neutron diffraction confirming stronger ordered moments and enhanced structural and thermal stability for the Ni0.75Co2.25O4 sample.

Development of aerial and belowground tubers in potato is governed by photoperiod and epigenetic mechanism - Kondhare, Kirtikumar R.; Kumar, Amit; Patil, Nikita S.; Malankar, Nilam N.; Saha, Kishan; Banerjee, Anjan K. (Plant Physiology, 2021)
Plants exhibit diverse developmental plasticity and modulate growth responses under various environmental conditions. Potato (Solanum tuberosum), a modified stem and an important food crop, serves as a substantial portion of the world's subsistence food supply. In the past two decades, crucial molecular signals have been identified that govern the tuberization (potato development) mechanism. Interestingly, microRNA156 overexpression in potato provided the first evidence for induction of profuse aerial stolons and tubers from axillary meristems under short-day (SD) photoperiod. A similar phenotype was noticed for overexpression of epigenetic modifiers-MUTICOPY SUPRESSOR OF IRA1 (StMSI1) or ENAHNCER OF ZESTE 2 (StE[z]2), and knockdown of B-CELL-SPECIFIC MOLONEY MURINE LEUKEMIA VIRUS INTEGRATION SITE 1 (StBMI1). This striking phenotype represents a classic example of modulation of plant architecture and developmental plasticity. Differentiation of a stolon to a tuber or a shoot under in vitro or in vivo conditions symbolizes another example of organ-level plasticity and dual fate acquisition in potato. Stolon-to-tuber transition is governed by SD photoperiod, mobile RNAs/proteins, phytohormones, a plethora of small RNAs and their targets. Recent studies show that polycomb group proteins control microRNA156, phytohormone metabolism/transport/signaling and key tuberization genes through histone modifications to govern tuber development. Our comparative analysis of differentially expressed genes between the overexpression lines of StMSI1, StBEL5 (BEL1-LIKE transcription factor [TF]), and POTATO HOMEOBOX 15 TF revealed more than 1,000 common genes, indicative of a mutual gene regulatory network potentially involved in the formation of aerial and belowground tubers. In this review, in addition to key tuberization factors, we highlight the role of photoperiod and epigenetic mechanism that regulates the development of aerial and belowground tubers in potato.

Polycomb group methyltransferase StE(z)2 and deposition of H3K27me3 and H3K4me3 regulate the expression of tuberization genes in potato - Kumar, Amit; Kondhare, Kirtikumar R.; Malankar, Nilam N.; Banerjee, Anjan K. (Journal of Experimental Botany, 2021)
Polycomb repressive complex (PRC) group proteins regulate various developmental processes in plants by repressing target genes via H3K27 trimethylation, and they function antagonistically with H3K4 trimethylation mediated by Trithorax group proteins. Tuberization in potato has been widely studied, but the role of histone modifications in this process is unknown. Recently, we showed that overexpression of StMSI1, a PRC2 member, alters the expression of tuberization genes in potato. As MSI1 lacks histone-modification activity, we hypothesized that this altered expression could be caused by another PRC2 member, StE(z)2, a potential H3K27 methyltransferase in potato. Here, we demonstrate that a short-day photoperiod influences StE(z)2 expression in the leaves and stolons. StE(z)2 overexpression alters plant architecture and reduces tuber yield, whereas its knockdown enhances yield. ChIP-sequencing using stolons induced by short-days indicated that several genes related to tuberization and phytohormones, such as StBEL5/11/29, StSWEET11B, StGA2OX1, and StPIN1 carry H3K4me3 or H3K27me3 marks and/or are StE(z)2 targets. Interestingly, we observed that another important tuberization gene, StSP6A, is targeted by StE(z)2 in leaves and that it has increased deposition of H3K27me3 under long-day (non-induced) conditions compared to short days. Overall, our results show that StE(z)2 and deposition of H3K27me3 and/or H3K4me3 marks might regulate the expression of key tuberization genes in potato.
Keywords: ChIP-sequencing; Epigenetics; PcG; photoperiod; polycomb repressive complex; potato tuberization; short-day; Solanum tuberosum; StE(z)2

Covalently interconnected layers in g-C3N4: toward high mechanical stability, catalytic efficiency and sustainability - Roy, Raj Sekhar; Mondal, Sanjit; Mishra, Samita; Banoo, Maqsuma; Sahoo, Lipipuspa; Kumar, Amit; Vinod, C. P.; De, Arijit K.; Gautam, Ujjal K. (Applied Catalysis B: Environmental, 2023)
The grim prospects for the industrial utilization of g-C3N4 nanosheets arise from multi-step processing resulting in low material yields and poor visible light response due to quantum confinement. Herein, we introduce a strategy for linking the adjacent layers of g-C3N4 covalently to realize a high surface area without excess mass loss in a one-step process by introducing diethylene glycol as a precursor that produces-(CH2)2-O-(CH2)2-linkers in-situ. Their presence increases interlayer spacing and introduces surface curvatures, discouraging the stacking of a larger number of layers to produce nanosheets with-3 times higher surface area. Interestingly, unlike other layered materials, the linkers also provide extraordinary mechanical stability against exfoliating forces. In addition, the process instills sub-bandgap states and a considerable visible light response at 500 nm to slow down the picosecond exciton recombination dynamics, resulting in-5 times enhancement in H2 generation efficiency from photocatalytic water-splitting over the bulk sample.
Keywords: Layer-linkers; Sustainable synthesis; Transient absorption spectroscopy; water-splitting

Speed breeding opportunities and challenges for crop improvement - Sharma, Shivani; Kumar, Amit; Dhakte, Priyanka; Raturi, Gaurav; Vishwakarma, Gautam; Barbadikar, Kalyani M.; Das, B. K.; Shivaraj, S. M.; Sonah, Humira; Deshmukh, Rupesh (Journal of Plant Growth Regulation, 2023)
Crop improvement in light of the rapidly changing climate and the increasing human population continues to be one of the primary concerns for researchers across the globe. The rate at which current crop improvement programs are progressing is essentially inadequate to meet the food demand. There is an urgent need for redesigning the crops for climate resilience and sustainable yield and nutrition. The rate of crop improvement is largely impeded owing to the long generation time taken by crop plants during the breeding process. As a solution in this direction, speed breeding is now being practiced at a large scale to reduce generation time to accommodate multiple generations of crops per year. To enhance the efficiency of breeding, researchers are now adopting an integrated approach where speed breeding is used along with modern plant breeding and genetic engineering technologies. In the present review, we have summarized the technological aspects, opportunities, and limitations associated with speed breeding. The application of speed breeding such as mapping population development, haplotype-based breeding, transgenic breeding, and genome-edited line advancement has also been discussed. Speed breeding is a promising technology that expedites the goals of food and industrial crop improvement by reducing the breeding cycles for establishing nutritional security and sustainable agriculture.
Keywords: Genome editing; Genomic selection; Haplotype breeding; Speed breeding; Transgenic breeding

β-catenin-driven innate and metabolic reprograming in macrophages fuel T-cell-dependent inflammation in Toxoplasma gondii infection: implications for therapeutic intervention - Kumari, Geetika; Kumar, Amit; Muduli, Rasmiranjan; Das, Mayami; Bhowmik, Prithwik; Singha, Biplab; Namdeo, Ankita; Dcosta, Criss; Wadhwa, Neerja; Maras, Jaswinder Singh; Kundu, Rakesh; Gupta, Nishith; et al. (Cell Death & Disease, 2026)
Toxoplasma gondii activates innate immunity via TLR11/12 in mice, but the lack of functional human counterparts leaves a gap in understanding parasite sensing in humans. Here, we bridge this gap by uncovering a host-intrinsic sensing mechanism, wherein beta-catenin signaling mediates immune recognition of T. gondii. Notably, this parasite hijacks the PI3K-AKT-beta-catenin pathway in macrophages to promote its replication. While beta-catenin ablation, either genetically or pharmacologically (XAV939), disavows this process, thereby inhibiting replication. Phospho-beta-catenin-TCF4 drives IRF4 transcription, followed by phosphorylation of IRF4, which regulates CYBB transcription. Augmented CYBB enhances mitochondrial-ROS and triggers mitophagy via PINK1/PARKIN, whereas ablation of beta-catenin preserves mitochondrial fitness, thereby impeding parasite growth. Enhanced ROS can oxidize host mitochondrial DNA, which then functions as a host-associated molecular pattern (HAMP). This activates the cytosolic pathogen recognition receptor (PRR) AIM2, triggering the AIM2-NLRP3-ASC-caspase-1-IL-1 beta inflammasome cascade. This cascade leads to gasdermin-D-mediated pyroptosis, a process that critically depends on the phosphorylation of beta-catenin. T. gondii's ASP5 protease plays an essential role in the phosphorylation of beta-catenin-mediated inflammasome activation. Metabolically, beta-catenin-dependent enhanced ROS stabilized HIF-1 alpha, which stimulates the HKII-LDH-A axis, promoting the Warburg effect, histone acetylation and pro-inflammatory M1-macrophage polarization (IL-12/IL-6/IL-23/TNF-alpha). beta-catenin ablation shifts metabolism to oxidative-phosphorylation, fostering M2-phenotype (IL-2/IL-10/TGF-beta) that abrogates parasites survival. beta-catenin also strengthens MHC-TCR avidity, driving Th1/Tc1, Th9/Tc9, and Th17/Tc17 paradigm, whereas beta-catenin inhibition promotes anti-inflammatory Th2/Tc2/Threg/Tcreg differentiation. Additionally, macrophage intrinsic beta-catenin dictates metabolic divergence in both CD4(+) and CD8(+)T-cells. Notably, beta-catenin-deletion in macrophages protects mice (beta-cat Delta M Phi) against infection, highlighting that XAV939 has therapeutic potential against toxoplasmosis.